Emerging technology solutions to support national emergency workforce capacity-building initiatives: lessons from Ugandan policy and practice - McMullen, Emily 1, 2, http://orcid.org/0000-0003-4898-1218Richard Price3, 2,3, Jonathan James3, Andrew Fryer4; Kamurari, Solomon; Mulimira, Moses; Jjingo, Daudi (Emergency Medicine Journal, 2025)
Trauma and emergency care is a national priority in Uganda due to the high burden of injury, impacting a primarily young and rural population. With a significant gap in qualified emergency medicine professionals, a need exists to rapidly upskill the current health workforce and to strengthen access to learning for non-specialist emergency care providers nationally. This review was completed in partnership with the Ugandan Ministry of Health and a consortium of UK partners to support national emergency workforce capacity building in Uganda and East Africa. The review built on policy and practice expertise to explore the feasibility of using emerging digital solutions, such as virtual and augmented reality, to meet the challenges of delivering rapid and equitable access to emergency care training at scale. Data collection included a narrative literature review, key informant interviews, an expert focus group, a technical workshop and field observations. Findings included (1) the identification of local technology expertise and experience, in direct contrast to literature and global perceptions of low-resource environments, (2) high and broad levels of national engagement with digital solutions, (3) existing ambition and infrastructure available to feasibly deliver training at scale and (4) delivery implications for comparable contexts. The review concludes that these emerging technologies should be considered a practical option in the design and delivery of health workforce training at scale. A series of recommendations are proposed for the policy and practice of health professional education and training in Uganda and for comparable contexts.